Analisis Pengaruh Bauran Pemasaran 7P terhadap Keputusan Pasien dalam Memilih Layanan Kesehatan di Rumah Sakit - Ulfa, Anisa Raudatul; Ernawaty, Ernawaty; Suraya, Andi Safutra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to explore the impact of implementing the 7P marketing mix on patient decisions in choosing healthcare services at hospitals. The method used is a literature review, utilizing the PRISMA diagram for article selection from Google Scholar and Scopus databases. The study filtered 1709 articles down to 6 relevant articles based on the topic and specified time period. The results indicate that all elements of the marketing mix—product, price, people, place, process, promotion, and physical evidence—significantly influence patient decisions, although the level of impact varies. The conclusion of this study is that the application of the 7P marketing mix significantly affects patients' choices in selecting healthcare services at hospitals. Keywords: Marketing Mix, 7P Marketing Mix, Hospital, Patient Decision.